Isolation of lactic acid bacteria as probiotic for humans / Mohamad Halif Mohamad Yusof - Mohamad Yusof, Mohamad Halif (2005)
In recent years, there has been considerable interest and research on the use of probiotics, for disease treatment or health promotion. However much remains to be done on the selection of strains that actually possess characteristics of true probiotic microorganisms.The present study was carried out to isolate potential probiotic organisms (lactic acid bacteria) that have antagonistic properties against human pathogens and could be used as bacteriotherapeutic agents to combat gastrointestinal disorders in humans. The sandwich overlay method was used to screen for antibacterial activity from four different kinds of fermented food (tapai pulut, rebung pekasam, budu and cincalok). Twenty one lactic acid bacterial (LAB) strains exhibited antibacterial activity in the preliminary screening. Eighteen of the LAB strains were able to inhibit E. coli but only four strains (Ti, T2, T7 and T12) had the ability to inhibit Staphylococcus aureus. Interestingly, T12 was able to inhibit S. aureus more effectively than Lactobacillus casei strain Shirota (a positive control) from Yakult. The antimicrobial substance produced by Tn was characterized, and the results demonstrated that the ability to inhibit S', aureus and E. coli was probably due to the production of organic acids and not bacteriocins.